Geospatial Intelligence to Support Intelligence Operations in Countering Terrorism: A Bibliometric Analysis (2000-2024) - Suteja, I Made Oges John; Persadha, Pratama Dahlian (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The method of movement of terrorist groups continues to evolve so that dealing with them cannot be done with conventional methods, but requires support from other approaches. Geospatial intelligence (Geoint) is one of the intelligence gathering techniques that can be used to determine the distribution of terrorist groups presented in an image of a particular area equipped with risks and potential threats posed. This research aims to describe the development of the use of Geoint method in handling terrorism. The method used in this research is bibliometric with data sources from Google Scholar in the period of 2000 to 2024 and the keywords ‘geospatial intelligence, geospatial information system (GIS)’ and ‘terrorism’. The results of this study show that the trend of studies on Geoint in supporting intelligence operations in handling terrorism has increased from the beginning of 2000 to 2023. As for 2024, it is still below the achievement in 2023, but still has the opportunity to increase because this period has not ended.